Hubungan Pengetahuan tentang Bahaya Merokok dengan Perilaku Merokok pada Remaja Putra di SMPN 06 Kota Jambi - Marta Suri; Vevi Suryenti Putri; Tri Husnul Lastari (Universitas Baiturrahim, 2023)
Teenagers start smoking for various reasons, such as imitating adult behavior, peer pressure, and imitating the traits of famous people who usually smoke. Adolescents who are likely to have low smoking behavior are adolescents whose family and friends do not smoke, are interested in academic activities or sports, and those who have plans to enter higher education, according to WHO (2018) every 6, 5 seconds one person dies from smoking. WHO research (2018) estimates that people who start smoking in their teens (70% of smokers at an early age) and continue smoking for 2 decades or more, will die 20-25 years earlier than people who have never touched cigarettes. This is the relationship between knowledge of the dangers of smoking and smoking behavior in young men at SMPN 06 Jambi City in 2021. This research was conducted on young men at SMPN 06 Jambi City which was carried out on August 4, 2021, this study was a quantitative study, with a cross sectional approach. Measuring tools using a questionnaire and the method of data collection by filling out a questionnaire. The population in this study was class VIII SMPN 06 Jambi City with a total of 179 students. With a sample of 63 respondents. The sampling method is using proportional random sampling technique and using univariate and bivariate analysis with chi-square statistical test. The results of research on smoking behavior from 63 respondents 54 respondents (85.7%) do not smoke, knowledge of the dangers of smoking from 63 respondents 46 respondents (73.6%) is high. The results of the statistical test show that there is a relationship between knowledge of the dangers of smoking and smoking behavior with a P-Value of 0.004 in young men at SMPN 06 Jambi City in 2021.It is hoped that the results of this study can increase outreach activities in the form of media leaflets, posters and banners about the dangers of smoking through school UKS in collaboration with the local health center.